Initial compensation contracts for new executives and financial distress risk: An empirical investigation of UK firms - Chen, Jie; De Cesari, Amedeo; Hill, Paula; Ozkan, Neslihan (Journal of Corporate Finance, 2018)
This paper analyses the effect of financial distress risk on the initial compensation contracts of new executives in the UK, where credit markets are more concentrated than in the US. We find that financial distress risk has a negative and statistically significant impact on the level of cash-based compensation and total compensation of executives, who are newly hired from either outside or inside the firm. This negative impact is accentuated in firms with a high fraction of bank debt, suggesting that banks, as creditors, provide monitoring and influence initial executive compensation packages in firms with high financial distress risk. Additionally, we find that financial distress risk has a negative and significant impact on the fraction of equity-based compensation for both externally and internally appointed executives.